The Effect of Addition of Limestone Powder and Fly – Ash on Land Classification - Agata Iwan Candra; Yosef Cahyo; Zendy Bima Mahardana (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2019)
The land is one of the absolute functions in every continuity of the activities of all living things on Earth. The issue of the low soil resilience type of montmorillonite activity indeed remains a problem in construction activities titled construction. Limestone and Fly-Ash is a formulation to change the classification value of montmorillonite soil activity in the following paper compilation research. Soil classification is an effort of the land grouping which is intended to separate the use of land carrying capacity which is more complex for each use of soil structure. The value of the basic soil activity used is 1.3, obtained from the plastic index calculation of 32.56 %divided by the sieve gradation value is smaller than the sieve number 200 by 25.7 %. Thus it shows that the soil structure used for testing is a type of Montmorillonite activity. with the addition of limestone powder additive materials and fly-ash showed activity value const soil structure to be late. In a combination of 5% additive soil activity type which was previously 1.3 (Montmorillonite classification) to 0.8 (Lilite classification), 10% additive to 0.7 (Lilite classification), 15% and 20% additive to 0.5 or Kaolinite classification.